Why have lending programs targeting disadvantaged small-business borrowers achieved so little succes in the United States? - Timothy Bates; Magnus Lofstrom; Lisa Servon (Institute for the Study of Labor (IZA), 2010)
Small business lending programs designed to move disadvantaged low-income people into business ownership have been difficult to implement successfully in the US context. Based in part on the premise that financing requirements are an entry barrier limiting the ability of aspiring entrepreneurs to create small businesses, these programs are designed to alleviate such barriers for low net-worth individuals with limited borrowing opportunities. Our analysis tracks through time nationally representative samples of adults to investigate the role of financial constraints and other factors delineating self-employment entrants from nonentrants. Paying particular attention to lines of business most accessible to adults lacking college credentials and substantial personal net worth, our analysis yields no evidence that financial capital constraints are a significant barrier to small-firm creation.
Keywords: J15; L26; 330; self-employment; entrepreneurship; micro-lending; Öffentliche Kreditvergabe; Unternehmer; Selbstständige; Wirkungsanalyse; Klein- und Mittelunternehmen; Verschuldungsrestriktion; USA